Numerical Simulation of Ventilation in a Confined Space - Kit L.W.; Mohamed H.; Luon N.Y.; Chan L. (Semarak Ilmu Publishing, 2024)
Numerical simulation of ventilation in a confined space is conducted with different quantities of heat sources and various conditions of the room with a constant ambient temperature of 298K. The velocity streamline plot shows a different air recirculating pattern in the case with the air ventilation system switched off. The room with an extreme condition achieves the highest temperature of T=310K. The lowest temperature is obtained in the case with a relaxing condition where T=Tac=294K. The efficiency of systems reduces when the air conditioner and air ventilation system operate at the same time. The efficiency of the air conditioner increases, and the ambient temperature achieves minimum value when the air ventilation system remains off. The position of the air conditioner is closed to the air ventilation system causing the efficiency of the system to reduce. This is due to the air ventilation system drawing cold air out of the room before convective heat transfer occurs. 2023, Semarak Ilmu Publishing. All rights reserved.